The association between congenital heart disease and small for gestational age with regard to the prevalence and outcomes. (24th October 2020) - Ishikawa, Takamichi; Uchiyama, Hiroki; Baba, Toru; Ohishi, Akira; Iijima, Shigeo; Iwashima, Satoru
Abstract: Aim: To evaluate the association between small for gestational age (SGA) and the prevalence of congenital heart disease (CHD) and the association of the SGA status with the outcomes among infants with CHD. Methods: Echocardiography was performed within the first 5 days of life in 5664 consecutive infants. Infants were classified into four groups according to the presence or absence of SGA and CHD. All CHD infants were followed up until either spontaneous resolution of all cardiac lesions, invasive intervention or death. All newborns without CHD were followed for mortality until the final follow‐up date. Results: A total of 303 infants were diagnosed with CHD, while 610 were diagnosed with SGA. Among the CHD infants, 56 were SGA, and 247 were not. A multivariable logistic regression analysis showed that the adjusted odds ratio of SGA (9.71, P < .001) was significantly higher than that of other parameters concerning predictors of invasive intervention or death. The mortality rate in the presence of both SGA and CHD (hazard ratio: 33.6, P < .001) was markedly higher than in the absence of both. Conclusion: SGA was a significant predictor of invasive intervention for CHD. The combination of CHD and SGA carried a high risk of death beyond that of either alone.